A reciprocal translocation dissects roles of Pax6 alternative promoters and upstream regulatory elements in the development of pancreas, brain, and eye. Issue 9 (23rd July 2013) - Elso, Colleen; Lu, Xiaochen; Weisner, Patricia A.; Thompson, Heather L.; Skinner, Andrea; Carver, Ethan; Stubbs, Lisa
<x xml:space="preserve">Abstract</x> Pax6 encodes a transcription factor with key roles in the development of the pancreas, central nervous system, and eye. Gene expression is orchestrated by several alternative promoters and enhancer elements that are distributed over several hundred kilobases. Here, we describe a reciprocal translocation, called 1Gso, which disrupts the integrity of transcripts arising from the 5′‐most promoter, P0, and separates downstream promoters from enhancers active in pancreas and eye. Despite this fact, 1Gso animals exhibit none of the dominant Pax6 phenotypes, and the translocation complements recessive brain and craniofacial phenotypes. However, 1Gso fails to complement Pax6 recessive effects in lacrimal gland, conjunctiva, lens, and pancreas. The 1Gso animals also express a corneal phenotype that is related to but distinct from that expressed by Pax6 null mutants, and an abnormal density and organization of retinal ganglion cell axons; these phenotypes may be related to a modest upregulation of Pax6 expression from downstream promoters that we observed during development. Our investigation maps the activities of Pax6 alternative promoters including a novel one in developing tissues, confirms the phenotypic consequences of upstream enhancer disruption, and limits the likely effects of the P0 transcript null mutation to recessive abnormalities in the pancreas and specific structures of the eye. genesis 51:630–646. © 2013 Wiley Periodicals, Inc.